Beberapa Faktor Risiko Kejadian Penyakit Ginjal Kronik (PGK) Stadium V pada Kelompok Usia Kurang dari 50 Tahun (Studi di RSUD dr.H.Soewondo Kendal dan RSUD dr.Adhyatma,MPH Semarang) - Ariyanto Ariyanto; Suharyo Hadisaputro; Lestariningsih Lestariningsih; Mateus Sakundarno Adi (Jurnal Epidemiologi Kesehatan Komunitas, 2018)
Background: Chronic Kidney Disease (CKD) stage V is an end-stage chronic kidney disease  characterized by glomerular filtration rate less than 15 mL /min /1.73 m2 and require dialysis  therapy. The purpose of this study to prove risk factors the occurrence of CKD Vin the age  group of less than 50 years.   Method: This study was a mixed method, case-control studies design were inforced with  indepht interview. Total respondents were 124 (62 cases and 62 controls) that taken by  consecutive sampling. Research instrument was a questionnaire interview. Data analysis using  univariate, bivariate (chi-square) and multivariate (logistic regression).                     Result: The variables that proved to be a risk factor for CKD V in the age group of less than 50 years were supplement energy drink consumption > 4 times/week (p=0.038; 95%CI = 1.063-7.944; OR=2.905), smoking ≥ 10 ciggarets/day (p=0.011; 95%CI=1.384-11.920; OR=4.061), and herbal medicine consumption > 4 times/week (p=0.007; 95%CI=1.431-9.949; OR=3.773). Variables that not proved were the consumption of coffee, supplements of vitamin C, soft drinks, alcohol, and NSAIDs. Qualitative results stated that the respondents consumed energy drink supplements to increase their stamina, smoke because it has become a habit, and consume herbal medicines because seen more natural and cure the sciatica fastly.Conclusion: Risk factors for the occurrence of CKD V in the age group of less than 50 years were the supplement energy drink consumption> 4 times/week, smoking ≥ 10 ciggarets/day, and the consumption of herbal medicine> 4 times/week.